The Use of Hybrid CO2+MQL in Machining Operations. (2015) - Pereira, O.; Català, P.; Rodríguez, A.; Ostra, T.; Vivancos, J.; Rivero, A.; López-de-Lacalle, L.N.
Abstract: Nowadays, the environmental concern in machining industry is a fact. Because of that, in this article a new cooling-lubrication system which combines CO2 cryogenic and MQL technologies is presented. The aim of this new cooling-lubrication system is to offer an ecological and economic efficient alternative. Two nozzle adapters are proposed with different CO2 outlets. The developed nozzles are Plug & Play and directly applicable to commercial MQL systems. The behaviors of nozzle adapters were simulated by CFD (Computational Fluid Dynamics) and the optimal nozzle adapter was tested by milling Inconel 718 ®. In these milling tests, the tool life was measured and using different main cooling-lubrication techniques: dry, wet, CO2 stand alone, MQL stand alone and CO2 +MQL (proposed alternative).